Early Growth of Improved Acacia mangium at Different Planting Densities - Arif Nirsatmanto (Institut Pertanian Bogor (IPB University), 2016)
Integrating tree improvement into silvicultural practices is essential in forest plantation. Concerning this fact, Acacia mangium spacing trial planted using genetically improved seed was established in West Java. This study was aimed to evaluate the impact of ages and planting density on early growth of improved seed A. mangium in the spacing trial. Improved seed from 2 seed orchards (SSO-5 and SSO-20) and a control of unimproved seed from seed stand (SS-7) were tested together in spacing 3 × 3 m and 2 × 2 m. Height, diameter, stem volume, and stand volume were observed at 3 ages. The results showed that improved seed consistently outperformed to unimproved seed. Ages were highly significant for all traits, but the significant difference varied among traits and seed sources for planting density and the interactions. High density performed better growth than low density at first year, and they were varied in subsequent ages depending on traits and seed sources. Improved seed from less intensity selection orchard was less tolerance to high density than that from high intensity selection orchard, but the tolerance was reversed in low density. Improved seed A. mangium from different level of genetic selection has responded differently in behavior to the changes of planting density.